Behavioral guidance for improving dental care in autistic spectrum disorders - Pastore, Irene; Bedin, Elena; Marzari, Giulia; Bassi, Francesca; Gallo, Claudio; Mucignat-Caretta, Carla (Frontiers in Psychiatry, 2023)
Introduction Autism spectrum disorders (ASDs) impair many aspects of everyday life and may prevent access to dental care, often limiting it to emergencies. Impaired oral health has long-lasting negative consequences on health status and on the acquisition of oral habits (e.g., oral respiration and grinding) or competencies (e.g., proper speech production). Children with ASD may be scared in the dental setting, which is rich in sensory stimuli and requires physical contact. Due to their behavioral manifestations, they represent a challenge for dentists and hygienists. We created a dedicated pathway with behavioral support for children with ASD to allow dental care and possibly limit the use of general anesthesia. Methods We evaluated the effects of behavioral support in a quasi-experimental design by comparing two groups of children with ASD. The first group (n = 84) was visited every 2 months for 3 years and received additional support (visual aids, caregiver training, and longer visit duration). A control group, matched for age and sex, was visited at least twice a year or more, if needed, according to standard healthcare guidelines. Results Compliance with the schedule was high throughout the 3 years. The degree of collaboration significantly improved after 1 year in the supported group, while the control group did not change. At the end of the study, collaboration remained significantly higher than at the beginning in the supported group. Half of dental treatments were possible without general anesthesia in supported children. No adverse effect was apparent on collaboration due to COVID-19 restrictions. Discussion Behavioral techniques improved the compliance of ASD children to regular dentistry visits and treatment. Furthermore, oral hygiene at home was similarly improved, addressing oral health from a lifelong perspective.